Erasmus student mobility and the construction of European citizenship. Issue 3 (2nd July 2016) - Llurda, Enric; Gallego-Balsà, Lídia; Barahona, Clàudia; Martin-Rubió, Xavier
Abstract : The Erasmus student mobility programme allocates three explicit objectives to the experience of spending a few months studying in another European country: (1) to benefit students educationally, linguistically and culturally; (2) to promote co-operation between institutions and (3) to contribute to the development of a pool of well-qualified, open-minded and internationally experienced future professionals [European Commission. 1996. The Obstacles to Transnational Mobility. Green Paper . http://aei.pitt.edu/1226/1/education_mobility_obstacles_gp_COM_96_462.pdf (accessed April, 2015)]. The programme has also sometimes been referred to as one of the most powerful tools of European integration. However, little research has so far been undertaken on how it may alter students' attitudes towards aspects of European identity and sense of European citizenship. Our study investigates the extent to which the Erasmus experience affects the sense of self as European citizens of a cohort of students from the University of Lleida (Catalonia, Spain). It also explores the students' position towards the notion of European citizenship and how this relates to the development of their plurilingual competence. Two questionnaires, one before and one after the study-abroad experience, provided quantitative data while qualitative data were obtained through the analysis of discussion groups focusing on aspects of European vs. national identity and citizenship.